Synergistic Effects of NOTCH/γ-Secretase Inhibition and Standard of Care Treatment Modalities in Non-small Cell Lung Cancer Cells - Sosa Iglesias, Venus; Theys, Jan; Groot, Arjan J.; Barbeau, Lydie M. O.; Lemmens, Alyssa; Yaromina, Ala; Losen, Mario; Houben, Ruud; Dubois, Ludwig; Vooijs, Marc (Frontiers in Oncology, 2018)
Background Lung cancer is the leading cause of cancer death worldwide. More effective treatments are needed to increase durable responses and prolong patient survival. Standard of care treatment for patients with non-operable stage III-IV NSCLC is concurrent chemotherapy and radiation. An activated NOTCH signaling pathway is associated with poor outcome and treatment resistance in non-small-cell lung cancer (NSCLC). NOTCH pharmacological small molecule inhibitors have been effective in blocking tumor growth and enhancing treatment effects in preclinical NSCLC models. However, a direct comparison of the effects of NOTCH inhibition when combined with the chemotherapeutics received by NSCLC patients, and chemoradiation regimens, is yet lacking. Methods Using two-dimensional monolayer growth assays, we screened 101 FDA-approved drugs from the Cancer Therapy Evaluation Program alone, or combined with radiation, in the H1299 and H460 NSCLC cell lines to identify potent treatment interactions. Subsequently, using multicellular three-dimensional tumor spheroid assays, we tested a selection of drugs used in clinical practice for NSCLC patients, combined these with a clinically approved small molecule inhibitor of the NOTCH pathway (BMS-906024) alone, or in combination with radiation, and measured specific spheroid growth delay (SSGD). Statistical significance between treatment groups was determined by one-way ANOVA with post-hoc Bonferroni correction, and synergism was assessed using two-way ANOVA. Results Monolayer assays in H1299 and H460 suggests that 21% versus 5% were synergistic, and 17% versus 11% were additive chemoradiation interactions, respectively. In H1299 tumor spheroids, significant SSGD was obtained for cisplatin, etoposide, and crizotinib, which increased significantly (p<0.05) after the addition of the NOTCH inhibitor BMS-906024, and especially in triple combination with not only BMS-906024 but also radiation. Chemotherapeutics from the taxane family (paclitaxel, docetaxel) increased their efficiency in triple combination but not in dual with BMS-906024. Synergistic interactions (p<0.05) were observed between BMS-906024 and chemoradiation (cisplatin, paclitaxel, docetaxel, and crizotinib). Similar results were observed for H460 spheroids using paclitaxel or crizotinib in dual/triple combination treatments. Conclusions Our findings point to novel synergistic combinations of NOTCH inhibition and chemoradiation that should be tested in in vivo NSCLC models to assess their ability to achieve tumor control and an improved therapeutic ratio.